Quantitative autoradiography in boron neutron capture therapy considering the particle ranges in the samples. (February 2021) - Takeno, Satoshi; Tanaka, Hiroki; Watanabe, Tsubasa; Mizowaki, Takashi; Suzuki, Minoru
Highlights: The microdistribution of boron is essential to the micro-scale dosimetry in BNCT. Autoradiography enables to quantify the spatial distribution of boron in tissue. We devise an equation for the empirical autoradiographic calibration curve. We also present a new co-localisation technique for autoradiographic images. The newly devised method is expected to provide new insights into BNCT. Abstract: Purpose: Boron neutron capture therapy is a cellular-scale particle therapy exploiting boron neutron capture reactions in boron compounds distributed in tumour cells. Its therapeutic effect depends on both the accumulation of boron in tumour cells and the neutron fluence. Autoradiography is used to visualise the micro-distribution of boron compounds. Methods: Here, we present an equation for the relationship between boron concentration and pit density on the solid-state nuclear track detector, taking into consideration the particle ranges in the samples. This equation is validated using liver-tissue sections and boron standard solutions. Moreover, we present a simple co-localisation system for pit and tissue-section images that requires no special equipment. Results: The equation reproduces the experimentally observed trends between boron concentration and pit density. This equation provides a theoretical explanation for the widely used calibration curve between pit density and boron concentration; it also provides a method to correct for differences of tissue-section thickness in quantitative autoradiography. Conclusions: Using the equation together with this co-localisation system could improve micro-scale quantitative estimation in tissue sections.